(2,2'-Bipyridyl-[kappa]2N,N')bis(N-butyl-N-methyldithiocarbamato-[kappa]2S,S')cadmium(II). - Jamaluddin, Nur Amirah; Baba, Ibrahim; Mohamed Tahir, Mohamed Ibrahim; Tiekink, Edward R. T. (International Union of Crystallography, 2011)
The CdII atom in the title compound, [Cd(C6H12NS2)2(C10H8N2)], is hexacoordinated by two dithiocarbamate ligands and the N atoms from a bidentate 2,2'-bipyridyl molecule. The coordination geometry is based on a distorted trigonal-prismatic arrangement of the N2S4 donor set. Supramolecular chains, aligned along the a-axis direction, are mediated by C-H...S interactions and these are connected into layers that stack along the c axis via [pi]-[pi] interactions [Cg(pyridyl)...Cg(pyridyl) = 3.6587 (13) Å].